2015
DOI: 10.1017/s1368980015002232
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Australian dietary guidelines during pregnancy: evidence from a national study

Abstract: Objective: To assess dietary intake of pregnant women against the Australian Dietary Guidelines with respect to the Five Food Group recommendations and determine predictors of adherence to the recommendations. Design: Cross-sectional web-based survey. Data were analysed using descriptive statistics and logistic regression. Setting: Pregnant women living in Australia. A national sample was recruited using an online panel provider and a South Australian sample was recruited through the antenatal clinic of a larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
52
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 31 publications
19
52
1
Order By: Relevance
“…In line with our results, several studies have found that only a small proportion of women consume the recommended number of vegetable servings per day, both pre-pregnancy [48] and during pregnancy [18, 35, 36, 44, 48, 49]. A national study from Australia showed that only 10% of pregnant women reported an intake of vegetables at or above recommendations [49]. Rodriguez-Bernal et al reported that 47% of Spanish women had an intake of vegetables which was below recommendations in first trimester of pregnancy [43], while a Finnish study found that only between 16 and 30% of pregnant women consumed the daily recommendations of FV [44].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In line with our results, several studies have found that only a small proportion of women consume the recommended number of vegetable servings per day, both pre-pregnancy [48] and during pregnancy [18, 35, 36, 44, 48, 49]. A national study from Australia showed that only 10% of pregnant women reported an intake of vegetables at or above recommendations [49]. Rodriguez-Bernal et al reported that 47% of Spanish women had an intake of vegetables which was below recommendations in first trimester of pregnancy [43], while a Finnish study found that only between 16 and 30% of pregnant women consumed the daily recommendations of FV [44].…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Blumfield et al found no evidence that women trying to conceive increased their consumption on nutrient rich foods such as FV [48]. In line with our results, several studies have found that only a small proportion of women consume the recommended number of vegetable servings per day, both pre-pregnancy [48] and during pregnancy [18, 35, 36, 44, 48, 49]. A national study from Australia showed that only 10% of pregnant women reported an intake of vegetables at or above recommendations [49].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Some pregnant women’s diets lack key nutrients, including folate, fiber, and iron 5. Their diets do not comply with official dietary guidelines with respect to consumption of some major food groups (including bread and cereals, fruit, vegetables, grains, and protein foods [nuts, beans, eggs, and fish]), and many are characterized as being high in processed meat, soft drinks, and takeaway foods 510…”
Section: Introductionmentioning
confidence: 99%